Relative measures in service research. Issue 6 (14th September 2015) - Aksoy, Lerzan; Hogreve, Jens; Lariviere, Bart; Ordanini, Andrea; Orsingher, Chiara
Abstract : Purpose: – The purpose of this paper is to introduce an alternative novel approach to measurement of customer perceptions of the service experience that links closely with customer loyalty outcomes. Design/methodology/approach: – This conceptual paper draws upon prior theory and empirical research to investigate the relevance of using relative metrics compared to absolute metrics in service research. Findings: – The findings upon which this paper draws upon show that measuring customer satisfaction, likelihood to recommend, brand preference using absolute metrics explain a very small per cent of the variance in key customer outcome measures such as share of wallet. Instead, a relative approach to these and other measures in service research is proposed. Practical implications: – Although business practice has embraced relative measurement much more extensively than has scientific research, the vast majority of customer experience measurement programs today continue to employ absolute measures resulting in suboptimal allocation of firm resources. This paper is a call to rethink these current measurement practices. Originality/value: – It is one of the first papers to argue for changing the widely employed use of absolute metrics in theory and practice in favor of relative metrics. Application to other service research theories is discussed.